(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the prevalence of depressive symptoms in pregnant women in developing countries in Asia, period 2012-2021. Methods: A systematic review, conducting a search and synthesizing the results of studies on depression in pregnant women in developing countries in Asia in the period 2012-2021. Results: 31 studies were included in the analysis. Among 34,657 pregnant women who participated in the study, there were 6943 pregnant women with depression symptoms, accounting for 20.03%. Conclusion: The rate of depression symptoms among pregnant women was still high. It is necessary to have appropriate intervention activities to improve the health status of pregnant women and newborn babies.